Intelligent Agent for Legal Health Case Automation: A Case Study in the Brazilian Public Sector - Rocha, L.; Amaro, B.; Furtado, V.; Duque, N.; Menezes, V.; Cláudio, J. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e Computacional, 2025)
This work presents the design, implementation, and evaluation of an intelligent agent developed to support the State Health Attorney’s Office of Ceará (PROSAÚDE) in managing over 3,000 monthly legal cases related to public health. The agent automates key decisions on legal contestation by interpreting court documents and applying internal legal norms. Built under the Judiciary vertical of Ceará’s Chief Scientist Program, the system combines large language models (GPT-4o), regulatory rule sets, and robotic process automation to extract medical/legal data, retrieve external sources (e.g., ANVISA), and generate official dispatches. It ensures consistent application of PROSAÚDE’s Internal Ordinance, which defines when appeals are required. Results show 98.4% precision in rule application and 93.8% recall in medication detection. In human-in-the-loop validation, 98.7% of dispatches required no revision. The solution highlights the potential of AI-driven legal automation to improve efficiency and accuracy in high-volume public workflows.